METHODOLOGICAL ASPECTS OF OVERCOMING THE CRISIS OF ARMENIAN STATEHOOD - Ayvazyan, Vardan (State and Law, 2025)
The object of the research is the genesis  of systemic conflicts in the paradigm of the formation of Armenian statehood, with its characteristic methodological and methodical approaches and features.The subject of the research is the main tendencies of forming Armenian statehood in recent history, the systemic crisis of state administration, the actual trajectory and structure of statehood formation.The scientific article presents the peculiarities of the cultural originality of the Armenian world in the field of state-building, its role in the world civilization. Parallel paradigms present the phenomenology of the clash of Armenian culture and anti-culture, on the basis of which the crisis of the Armenian statehood is diagnosed, which led to the painful defeat of our country in the 44-day war, disrupted the international legal capacity of our state. At the same time, the article proposes complex methodological solutions to overcome the crisis of Armenian statehood.The main conclusion of the work is that now, more than ever, the Armenian world needs a spiritual relaunch. It is what is capable of crystallizing the intellectual potential of Armenia, of moving the Armenian people from identity to self-identification, of giving meaning to the standards of Armenian quality.
Keywords: аrmenian world; culture; crisis; statehood; war; civilization; genocide; rebirth; systemic conflict